Ovonic Threshold‐Switching GexSey Chalcogenide Materials: Stoichiometry, Trap Nature, and Material Relaxation from First Principles. Issue 5 (11th February 2020) - Clima, Sergiu; Garbin, Daniele; Opsomer, Karl; Avasarala, Naga S.; Devulder, Wouter; Shlyakhov, Ilya; Keukelier, Jonas; Donadio, Gabriele L.; Witters, Thomas; Kundu, Shreya; Govoreanu, Bogdan; Goux, Ludovic; et al.
Abstract : Density functional theory simulations are used to identify the structural factors that define the material properties of ovonic threshold switches (OTS). They show that the nature of mobility‐gap trap states in amorphous Ge‐rich Ge50 Se50 is related to GeGe bonds, whereas in Se‐rich Ge30 Se70 the Ge valence‐alternating‐pairs and Se lone‐pairs dominate. To obtain a faithful description of the electronic structure and delocalization of states, it is required to combine hybrid exchange–correlation functionals with large unit‐cell models. The extent of localization of electronic states depends on the applied external electric field. Hence, OTS materials undergo structural changes during electrical cycling of the device, with a decrease in the population of less exothermic GeGe bonds in favor of more exothermic GeSe. This reduces the amount of charge traps, which translates into coordination changes, an increase in mobility‐gap, and subsequently changes in the selector‐device electrical parameters. The threshold voltage drift process can be explained by natural evolution of the nonpreferred GeGe bonds (or "chains"/clusters thereof) in Ge‐rich Ge x Se1– x . The effect of extrinsic doping is shown for Si and N, which introduce strong covalent bonds into the system, increase both mobility‐gap and crystallization temperature, and decrease the leakage current. Abstract : Density‐functional theory investigations on amorphous Ge x Se y ‐based chalcogenides show that the mobility‐gap trap states change their nature with Ge:Se ratio, applied electric field, and aging. Changes in the mobility‐gap trap concentration during selector‐device operation has a detrimental influence on the threshold voltage. Si/N doping strategy shows improvement in crystallization temperature and leakage current.